On the measurement of scientific performance: Do we really need to take the distribution of citations into account? - Crespo, N.; Simões, N. (International Journal of Information Science and Management, 2021)
Despite the drawbacks already pointed out and the wide set of variants suggested to overcome some of them, the ℎ-index is the most used measure to conduct the author-level scientific evaluation. Simplicity is probably its main advantage and the reason for its popularity. The main goal of the current study is to propose an index that is directly linked and almost perfectly correlated with the ℎ-index but is even simpler to obtain. Our index does not require any form of calculation. It disregards the distribution of citations among the papers of the author. Instead, only the total number of papers and the total number of citations of the author is used to obtain the final score. The score of each author can be seen in the table we present in this study. Although much simpler than the ℎ-index (and other measures that account for citation distribution), our index produces the same general conclusions. We illustrate the application of this index with a sample of economists.